Monitoramento clínico do processo inflamatório periapical antes e após o uso de diferentes medicações intracanal através dos níveis de biomarcadores inflamatórios - Teixeira, Flávia Figueiredo Chaves [UNESP] (2015)
The aim of this study was: 1) To investigate the inflammatory profile of apical periodontitis disease present in primarily infected root canals determined by the levels of inflammatory cytokines : IL-1beta, IL-6, TNF-alfa; and to correlate with the presence of clinical features; 2) To investigate the levels of metalloproteinases [MMP-1, -2, -9], metalloproteinase inhibitors [TIMP-1 e -2] ; complexes MMP/TIMP [MMP1/ TIMP1, MMP1/TIMP2, MMP2/TIMP1, MMP2/TIMP2, MMP9/TIMP1 e MMP9/TIMP2], present in apical peridontitis disease from teeth with primary endodontic infection; and to correlate with the presence of clinical features; 3) To correlate the levels of IL-1beta, IL-6, TNF-alfa with their respectively antagonists - IL1-RA, IL6-RA, s TNF-R1, all present in apical peridontitis; 4) To evaluate the effectiveness of different root canal medications in the inflammatory process by monitoring the levels of inflammatory cytokines [IL-1beta, IL-6, TNF-alfa], MMP's [MMP-1,-2,-9]; TIMP [TIMP-1 and -2] and complexes [MMP1/TIMP1, MMP1/TIMP2, MMP2/TIMP1, MMP2/TIMP2, MMP9/TIMP1 e MMP9/TIMP2] in apical periodontitis. Twenty patients with single-rooted teeth that had necrotic pulp and periapical periodontitis will be selected. After BMP teeth will be randonly devided into 2 groups according to the root canal medication selection: Ca(OH)2+SSL [Ca(OH)2 + Saline Solution]; e Ca(OH)2+CHX [Ca(OH)2 + chlorhexidine gel 2%]. Samples will be collected from intersticial fluid by using sterile/ apyrogenic paper points. Samples will performed at two diferente times: After chemomechaical preparation (S1) and after 14 of root canal medication (S2). Inflammatory cytokines, metalloproteinases and their antagonists will be dosage by ELISA-assay. The levels of inflammatory cytokines, metalloproteinases and their antagonists will be typed on a spreadsheet and statiscally analyzed by SPSS for Windows and Statistic packpage 9.0. ...